ANALISIS PENGARUH PERFORMANCE, SIZE, INEFISIENSI, CAPITAL, DAN DANA PIHAK KETIGA TERHADAP NON PERFORMING LOAN (Studi Pada Bank Umum Konvensional Go Public di Indonesia Periode 2011-2015) - Gunawan P., Andreas Gunawan P; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2016)
Financial Intermediary is a primary function of banks as a conduit of funds (credit) to the public in order to improve the economy. But often external shocks such as higher interest rates and a depreciation of rupiah hamper banks control the credit decision. To be able to withstand external shocks, certainly needed a good foundation of internal management in banking itself. The purpose of this study was to determine how much influence the internal banking foundation which is reflected by the Performance, Size, Inefficiency, Capital and Third Party Funds variables to the Non-Performing Loan (NPL) in the Conventional Commercial Bank 2011-2015.This research using a sample of 28 Conventional Commercial Bank Go Public in Indonesia. The data used in this study of secondary data from annual reports and the publication of financial statements of banks that have met the criteria of samples (purposive sampling). This research has been qualified for use multiple linear regression model.Results of the analysis showed that the Performance and Capital did not have a significant influence on the Non-Performing Loan (NPL). Meanwhile Size, Inefficiency, as well as Third Party Funds proved to have a significant influence on the Non-Performing Loan (NPL). The predictive ability of these variables in explaining the Non-Performing Loan (NPL) by 23%, while the remaining 77% are influenced by other factors not included in the research model.